Proceedings of tumor board meeting - Sushmita Bhatnagar; Manish Madhav (Wolters Kluwer Medknow Publications, 2012)
The Tumour Board Meeting was held on August 16, 2011, in the Seminar Hall at B.J. Wadia Hospital for children. The panelists of the meeting were Dr. S. Ranganathan, Pediatric Pathologist from Children's Hospital of Pittsburgh; Dr. Archana Swami, Consultant Pediatric Oncologist at Wadia Children's Hospital; Dr. Sajid Qureshi Onco-surgeon (Pediatric) at Tata Memorial Hospital and Dr. Sushmita Bhatnagar.